Natureza jurídica da decisão que julga a desconsideração da personalidade jurídica no processo civil: extensão e limites - Longo, Caricielli Maísa (2018)
This paper deals with the issue of reflecting on the nature, extent and limits of the judicial decision, which recognizes or not the disregarding of the legal personality. Furthermore, it analyzes the impacts that such a decision will create within and out of the legal action in the event of a discussion for a likely inclusion of a partner or partnership, which will depend on the kind of disregarding aimed. Thus, the purpose of this thesis is to analyze the content of the judicial decision that grants or not the disregarding of the legal personality. From a practical point of view, it is important to establish a thesis along this line. In spite of the concern to attain procedural effectiveness, that in most cases is only obtained with the gratification of receiving a credit, as will be shown, this effectiveness cannot be obtained at any price. There is a long-standing crisis in Brazil, a serious crisis of both default and abuse of rights, in which often times, people who should not be held responsible for an obligation, are hit by the simple fact of integrating a society or undertaking an economic activity. Likewise, in relation to the default crisis, there are several devices employed by individuals, who use the veil of the legal person and the inherent autonomy of it to create a look of neatness. This, however, hides an iniquitous attitude in which the partner uses the figure of society to obtain spurious gains. Thus, it is essential to make sure to what extent the decision that disregards the personality of the legal person will affect the partners, what the nature of that decision is, as well as its extent and limits